PATTERN OF TRANSFORMATION OF DSN-MUI FATWA REGARDING MUSYARAKAH MUTANAQISAH CONTRACTS IN LEGISLATION (DSN-MUI FATWA ANALYSIS NUMBER: 01/DSN-MUI/X/2013): Pola Tansformasi Fatwa DSN-MUI Tentang Akad Musyarakah Mutanaqisah Dalam Peraturan Perundang-Undangan (Analisis Fatwa DSN-Mui Nomor: 01/DSN-MUI/X/2013) - WAHYU NITA SARI; Khumedi Ja’far; Khairuddin (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2021)
Departing from the growing assumption that there is a change between the provisions of the DSN-MUI fatwa and the POJK regarding the purpose of musyarakah mutanaqishah financing, namely from productive to consumptive. musyarakah mutanaqishah must be aimed at financing with productive characteristics such as working capital, consumptive purposes such as mortgage financing. Because of this, several perceptions have emerged in the public which say that there is a discrepancy between the fatwa and the laws and regulations. Therefore, the research is directed to see how the pattern of transformation of the DSN-MUI Fatwa regarding the Musyarakah Mutanaqishah Agreement on the Legislation. The results of this study found that the transformation pattern here can be classified into two; literally and non-literally. literal use of positivization and copy paste methods, and non literal method of objectification with adoption and adaptation patterns Literally and Islamic law (DSN-MUI fatwa) does not have to be literally transformed into laws and regulations. The results of this study found that the problem, especially the transformation caused by the positivization pattern of the fatwa that was not appropriate, was partially adopted and implemented. The content mostly uses the same concepts as conventional ones. As for the substance of the problems caused by the habit of taking fatwas that are not complete (partial only) and there are new fatwas that elaborate on old concepts.